Corrosion resistance of the nickel‐free high‐nitrogen steel FeCrMnMoN0.9 under simulated inflammatory conditions. Issue 6 (7th November 2020) - Radice, Simona; Impergre, Amandine; Fischer, Alfons; Wimmer, Markus A.
Abstract: Nickel‐free, high‐nitrogen austenitic steels (AHNS) have been introduced for biomedical applications, with encouraging results in terms of mechanical and corrosion properties. Here, we tested the corrosion resistance of a nickel‐free high nitrogen steel (FeCrMnMoN0.9) in bovine serum solutions containing 0 or 3 g/L hyaluronic acid (HA), and 0, 3, or 30 mM hydrogen peroxide (H2 O2 ) simulating no, moderate, or strong inflammatory conditions, respectively. Nondestructive electrochemical measurements (open circuit potential [OCP], linear polarization resistance " R P ", and electrochemical impedance spectroscopy) were run in triplicate over 10 hr. The presence of HA had no significant effect either on the stabilized OCP values, or on the corrosion resistance of FeCrMnMoN0.9. Increasing H2 O2 concentrations shifted the OCP to more electropositive values; the corrosion resistance decreased only at a 30 mM H2 O2 . Final R P values at 0, 3, and 30 mM H2 O2 resulted in 1598 ± 276, 1746 ± 308, and 439 ± 47 kΩ cm 2, respectively. These values were 4–14 times higher, than the R P values measured on LC‐CoCrMo in our previous study, conducted under identical conditions. While these findings are encouraging, future studies need to focus on tribocorrosive properties of the AHNS to evaluate its applicability in joint replacement.